Improving quality of dragon fruit (hylocereus costaricensis) syrup by processing with double jacket vacuum evaporator. Issue 1 (November 2021) - Susilo, B; Sutan, S M; Hendrawan, Y; Damayanti, R
Abstract: Red dragon fruit ( Hylocereus costaricensis ) is a famous fruit because of its high nutritional content. Although the product diversification of red dragon fruit is quite a lot, however, this product has limited information as a syrup product. The evaporation process for making syrup at the traditional level is usually carried out at high temperatures which results in the high destruction of nutritional content and reduces the quality of syrup. The study of the evaporation process at low temperature and low pressure using a double jacket vacuum evaporator for manufacturing red dragon fruit syrup was conducted in this research in order to improve product quality. The aims of this study are to evaluate the effect of temperature process and vacuum pressure on the quality of red dragon fruit ( H.costaricensis ) syrup using a double jacket vacuum evaporator and to know the optimum temperature process and vacuum pressure to producing red dragon fruit sirup with higher content of vitamin C. The double jacket evaporator operates at a pressure lower than atmospheric pressure so that there were 9 treatment combinations. The result showed the temperature gave a highly significant effect, especially on vitamin C. It also gave on moisture content and reducing sugar. The temperature gave no significant effect on total sugar content. Whereas, the pressure gave a significant on moisture content, but not gave a significant on vitamin C, reducing sugar content and total sugar content. However, the best treatment for optimum vitamin C is 50 0 C/-60 cmHg with 8.75 mg/100 ml.